Profil Lipid Penderita Acquired Immunodeficiency Syndrome (AIDS) di Kota Bau-Bau Sulawesi Tenggara - Angriani Fusvita (Jurnal Kesehatan Vokasional, 2019)
Background: Based on data on cases of deaths from AIDS in Southeast Sulawesi Province, the highest number of AIDS deaths was found in the city of Bau-bau. Metabolic related disorders are common in people with HIV / AIDS, namely insulin resistance, lipodystrophy, and dyslipidemia. Research conducted by Adewole et al. (2010) explains that in people infected with HIV, they have shown various lipid abnormalities.Objective: to find out the lipid profile of AIDS patients in the city of Bau-bau Southeast Sulawesi.Method: This type of research is descriptive in cross-sectional study by examining lipid profiles in AIDS patients as many as 29 people as samples in the city of Bau-bau with a continuous flow analyzer method. Samples are obtained by accidental sampling method. Data were analyzed descriptively.Results: HDL levels in AIDS patients were low (≤ 45 mg / dL) as many as 29 people (100%). Cholesterol levels in AIDS patients have normal results (≤ 200 mg / dL) as many as 29 people (100%). LDL levels in normal AIDS patients (≤ 130 mg / dL) are 29 people (100%). Triglyceride levels in AIDS patients were high (200 mg / dL) as many as 29 people (100%).Conclusion: Lipid profiles in AIDS patients found high triglyceride levels, normal LDL and cholesterol levels, and low HDL levels in AIDS patients